A Preliminary Screening Tool for High-Risk Frailty in Older Adults Patients with Pulmonary Tuberculosis - Li HJ; Zhou YY; Yu HH; Jiang J; Cai YW (Clinical Interventions in Aging)
Hui-Juan Li, Yue-Ying Zhou, He-He Yu, Jian Jiang, Yu-Wei Cai Department of Infectious Diseases, Wenzhou Central Hospital, Wenzhou, People’s Republic of ChinaCorrespondence: Yue-Ying Zhou, Department of Infectious Diseases, Wenzhou Central Hospital, No. 252 Baili East Road, Lucheng District, Wenzhou City, 325000, People’s Republic of China, Tel +86-0577-88882121, Email zhouyueying25@163.comObjective: To understand the current status and analyse the factors influencing frailty in older adults patients with pulmonary tuberculosis.Methods: This retrospective case-control study included 204 older adults patients with pulmonary tuberculosis. The enrolled patients were divided into a frailty group (n = 101) and a non-frailty group (n = 103). The study further collected and compared the data of various scores.Results: The total frailty score among the patients ranged from 0 to 15 points, with an average score of 5.23 ± 2.31 points. The total social support score ranged from 15 to 47 points, with an average of 33.43 ± 6.11 points. The physical function level scores ranged from 10 to 100 points, with an average of 84.58 ± 14.48 points. Additionally, univariate analysis showed significant differences between the groups in terms of age, body mass index (BMI), duration of disease, types of long-term medication and the number of complications and comorbidities (P < 0.05). Correlation analysis revealed negative correlations of social support (P < 0.001) and physical function (P < 0.001) with the overall frailty score and a positive correlation of depression levels (P < 0.001) with the overall frailty score. Further regression analysis indicated that being over 80 years old, having a low BMI, long-term polypharmacy and a high depression score were risk factors. High social support and physical function scores were protective factors against frailty in older adults patients with pulmonary tuberculosis.Conclusion: In older adults patients with pulmonary tuberculosis, the overall frailty score shows negative correlations with social support and physical function and a positive correlation with depression level.Keywords: pulmonary tuberculosis, frailty, older adults, risk factors